BIOCENOTIC RELATIONSHIPS OF aYELMINTHS WITH DOMESTIC POULTRY (Scientific journal of the Fergana State University, 2025)
This study focuses on the biocenotic relationships between helminths and domestic poultry in the Fergana Valley. The research analyzes the ecological and faunal characteristics of helminths, their effects on poultry health, and the extent of infestation. Particular attention is given to the role of intermediate hosts in the helminths’ life cycles and their adverse impact on bird health. The findings provide a significant scientific basis for developing effective preventive measures aimed at mitigating the negative effects of helminths on poultry productivity, including egg production and meat yield.